The Impact of Brand Equity towards Customer Loyalty of Starbucks: Testing the Role of Customer Satisfaction as the Mediate Variable - Helen Ongkowidjoyo (iBuss Management, 2015)
With the fact of tight competition in café industry in Surabaya, Starbucks in Surabaya also needs to improve its performance to be able to compete with the current competition, to grow more in the market, and to be sustained in Surabaya. One of the things that be done is by improving the brand equity so that it can improve customer satisfaction and customer loyalty. This research would like to find the impact of brand equity towards customer loyalty as well as testing the customer satisfaction mediating effect. By distributing 228 questionnaires spread around Surabaya via online through the Google form and by conducting sobel test, this research has proven that brand equity has a positive impact towards customer loyalty and customer satisfaction is proven to have a mediating impact.Keywords: Brand Equity, Customer Satisfaction, Customer Loyalty, Starbucks